V2 : Institute for the unstable media - V2_ (2006)
[Dt.:] V2 wurde 1981 in Rotterdam von einer Gruppe Medienkünstlern als ein Zetrum für Kunst- und Medientechnologie gegründet. Der Fokus von Ausstellungen und Veranstaltungen liegt auf zeitgenössischer Medienkunst. Die Website informiert über Veranstaltungen (Workshops, Vorträge etc.) und Veröffentlichungen. Über eine Datenbank steht das Archiv von V2 von 1993 bis heute zur Verfügung. - [Engl.:] V2 was founded in 1981 in Rotterdam by a group of multimedia artists, as an interdisciplinary centre for art and media technology. Events concentrates its efforts on the presentation of contemporary media art by organizing exhibitions, lectures, workshops, master classes, symposiums and performances. The site gives information on its activities and maintains an archive portal, where information about V2's activities from 1993 onwards can be found.